Galectin-3 in recipients with kidney graft dysfunction: analysis of predictive significance - D. A. Velikiy; S. O. Sharapchenko; O. E. Gichkun; E. S. Stolyarevich; D. A. Saydulaev; M. A. Osoblivaya; A. A. Mamedova; O. P. Shevchenko (Вестник трансплантологии и искусственных органов, 2024)
One of the most pressing issues in contemporary transplantology is the ongoing search for less invasive methods that would identify potential complications that recipients of solid organ transplants may encounter. Profibrogenic factor galectin-3 (Gal-3) is a potential marker of such complications. It is presumed that it may be involved in regulatory processes in both physiological and pathological conditions; Gal-3 is of particular importance in diseases associated with chronic inflammation and fibrosis.Objective: to assess the predictive significance of Gal-3, determined in the recipients’ serum, in the pathology of a transplanted kidney.Materials and methods. The study included 138 kidney recipients aged from 5 to 68 years and a group of healthy individuals (n = 11). Recipients’ serum Gal-3 levels were measured by immunoenzymatic method.Results. Among the kidney recipients, 91 patients had kidney graft dysfunction according to laboratory and clinical data, which served as an indication to perform a graft biopsy with morphologic examination of the samples. In kidney recipients, Gal-3 levels were significantly different and higher than in healthy individuals, p = 0.017; it did not correlate with most blood test parameters, but there was an inverse correlation with graft glomerular filtration rate (GFR) (r = –0.174; p = 0.043). Recipients’ Gal-3 levels were independent of their tacrolimus blood levels. Kidney recipients with graft dysfunction had considerably higher Gal-3 levels (p = 0.0003) compared to those without. Comparative analysis significantly showed higher Gal-3 concentrations in recipients with acute cellular rejection (ACR, p = 0.005), antibody-mediated rejection (AMR, p = 0.016) and сalcineurin inhibitor (CNI) nephrotoxicity (p = 0.006) compared to recipients without dysfunction. Recipients with signs of CNI nephrotoxicity tended to have higher Gal-3 levels when compared to recipients with graft dysfunction of other etiology (p = 0.08). Kidney recipients with Gal-3 levels above the calculated threshold value of 7.63 ng/mL had a 2.89-fold higher risk of developing chronic graft dysfunction and/or requiring hemodialysis compared with the rest of the kidney recipients (RR = 2.89 ± 0.46 [95% CI 1.17–7.11]), with 76.2% sensitivity and 56.1% specificity of the test.Conclusion. The threshold serum Gal-3 level in kidney recipients can be considered a predictor of an unfavorable graft outcome (chronic graft dysfunction and/or a need for renal replacement therapy).